Proceedings of the 1st International Conference on Sustainable Management and Innovation, ICoSMI 2020, 14-16 September 2020, Bo 2021
DOI: 10.4108/eai.14-9-2020.2304409
|View full text |Cite
|
Sign up to set email alerts
|

Startups Business Opportunities Analysis as an Effort to Arrange Policy Design for Reducing the Impact of Covid-19 Pandemic on Startups Business

Abstract: Covid-19 pandemic had an impact on the global economy. Startups played big role in Indonesia's economy. This study was aimed to know the startups business opportunity during pandemic. This study used online questionnaires to the startups under the coordination of the Ministry of Research and Technology. Questionnaire were processed using pivot tables and analyzed by SWOT. Data showed that 79% startups keep survive despite the pandemic conditions. This study was focus on startups in the field of health/medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The importance of managing turnover intention became even more crucial to sustain business for startups with limited resources during the COVID-19 pandemic. The research of Widiyanto, et al (2021) found that 21% of startups stopped operating and have declared bankruptcy since the pandemic started, most of them are digital startups. One of the reasons stated by startups' founders was the lack of human resources (Widiyanto, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of managing turnover intention became even more crucial to sustain business for startups with limited resources during the COVID-19 pandemic. The research of Widiyanto, et al (2021) found that 21% of startups stopped operating and have declared bankruptcy since the pandemic started, most of them are digital startups. One of the reasons stated by startups' founders was the lack of human resources (Widiyanto, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The research of Widiyanto, et al (2021) found that 21% of startups stopped operating and have declared bankruptcy since the pandemic started, most of them are digital startups. One of the reasons stated by startups' founders was the lack of human resources (Widiyanto, et al, 2021). During the pandemic, the Indonesian government enforced law that forced companies to apply the work-from-home system.…”
Section: Introductionmentioning
confidence: 99%
“…Besides agri-food supply chain, digital technologies have been harnessed to support micro, small, and medium-sized enterprises (MSMEs) and startups development in Indonesia, such as: business model, sustainability, policy design, and entrepreneurial ecosystem (Fitriasari 2020, Winarsih et al 2020, Purbasari et al 2020, Widiyanto et al 2021). Furthermore, the Indonesia Development Forum (2021) reported that 24% of Indonesia's MSMEs have entered digital platforms than the MSMEs recorded before the pandemic, namely only at 13% or around 8 million businesses.…”
Section: Introductionmentioning
confidence: 99%